The onset of alloying in Cu-Ni powders under high-shear consolidation. (1st December 2021) - Overman, N.R.; Olszta, M.J.; Bowden, M.; Li, X.; Rohatgi, A.; Mathaudhu, S.N.; Grant, G.J.; Whalen, S.A.
Graphical abstract: Highlights: Friction consolidation of Cu-Ni powders has revealed unique paths toward alloying. High shear processing conditions illuminate disparate material properties. Strength, modulus, and hardening variations alter load transfer and alloying pathways. Infiltration of Cu along Ni-Ni high angle grain boundaries and asymmetric diffusion were observed. Abstract: Friction consolidation (FC) is a solid phase processing methodology that densifies a material through high-shear deformation and pressure at elevated temperature. The method has garnered interest in the scientific community because of its ability to produce extremely refined and homogeneous microstructures, off-axis texture development, and improved material properties. This manuscript presents an investigation of Cu and Ni material mixing via evaluation of morphological evolution, grain boundary characterization, and compositional analysis to provide insights on the operational alloying mechanisms occurring under high shear and elevated temperature. Using correlative microscopy techniques, we show alloying progresses via a combination of grain boundary diffusion and interfacial roughening at heterophase boundaries. Evidence supporting Cu infiltration along Ni-Ni grain boundaries along with asymmetric diffusion of Cu into Ni grains is highlighted. The resultant, consolidated microstructure was produced directly from a powder compact in ∼30 s and exhibited a submicrometer, equiaxed grain size.